The Effect of Sex, Math's Anxiety and Language on Working Memory Perfomance - Afentouli Panagiota; Papazoglou Panagiota (2017)
Declaration, Acknowledgements, Abstract, Introduction, Aim, Rationale and Hypothesis, Method, Design, Participants, Apparatus, Math's Anxiety Scale (MAS-UK) and Marking, Calculations, Reading Span Task (RST) and Marking, Procedure, Analytic Strategy, Ethics, Results, Data Screening, Descriptive Statistics and Inferencial Statistics, Hypothesis, Discussion, Implications, Strengths and Limitations, Futire Research, Conclusion, Appendices, Personal Development Planning.